2013
DOI: 10.1097/iae.0b013e31828abe50
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Outcomes, and Prognostic Indicators of Fall-Related Open Globe Injuries

Abstract: Fall-related OG injuries can lead to severe ocular morbidity especially in the elderly patients. They carry a worse visual prognosis compared with other injuries, which emphasizes on the importance of protective measures in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
3
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 21 publications
4
25
3
2
Order By: Relevance
“…This rate was reported to be 20.1 to 100% in severe OGIs in the literature. 5,7,8,10,13,14 Hyphema was a prognostic factor for poor final VA (P = 0.009) in our study. Rofail et al 3 reported hyphema was a predictor of poorer visual outcome.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This rate was reported to be 20.1 to 100% in severe OGIs in the literature. 5,7,8,10,13,14 Hyphema was a prognostic factor for poor final VA (P = 0.009) in our study. Rofail et al 3 reported hyphema was a predictor of poorer visual outcome.…”
Section: Discussionsupporting
confidence: 52%
“…8 However, some studies found no association between vitreous hemorrhage and visual outcome. 6,13,14 Feng et al 10 considered that severe intraocular hemorrhage was not only a predictor of an unfavorable outcome, but also a reflection of the seriousness of the ocular damage, which includes severe intraocular tissue injury, such as to the choroid and retina. In our study, retinal detachment was detected in 40.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Fall-related open globe injuries are seen in women and elderly patients more frequently. [9][10][11][12] It was reported that 14% of open globe injuries are related with falling and 64 % of the all patients were 65-year-old and older. 11 There are many studies about eye injuries that had occured days or many years after extracapsular cataract surgery (ECCE) and IOL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] It was reported that 14% of open globe injuries are related with falling and 64 % of the all patients were 65-year-old and older. 11 There are many studies about eye injuries that had occured days or many years after extracapsular cataract surgery (ECCE) and IOL implantation. 12 Kloek et al reported that 7% of open globe injuries were because of dehiscence of cataract wound; and 89% of these injuries were in patients that had cataract surgery by ECCE.…”
Section: Discussionmentioning
confidence: 99%